Penerapan Metode Operational Competitiveness Rating Analysis (OCRA) Dalam Keputusan Rekomendasi Mutasi Jabatan Karyawan - Hasibuan, Surya Sintamie (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Position in a company is a level that is very influential on the value of responsibility for the work that must be done to achieve a mission that is targeted by the company. Giving certain positions to employees in a company must of course be based on benchmarks that are the provisions of the leadership of the company. The problems that occur in PT. Wira Agung's creation to carry out the employee job transfer process is the difficulty in making real decisions as expected because the assessment process for employees who will undergo a job transfer is objective. To solve this problem, the author builds a visual-based decision support system using the Visual Basic Net 2008 programming language by applying the Operational Competitiveness Rating Analysis (OCRA) method. The results of this study are expected to be a solution for recommendations for employee transfers at PT. Kreasi Wira Agung.